Pengaturan Jarak Bola (Sphere Gap) Pembangkitan Tegangan Tinggi Impuls Secara Semi Otomatis - Sonong Sonong; Muhammad Yusuf Yunus; Marhatang Marhatang; Makmur Saini; Herman Nawir; Muhammad Ruswandi Djalal (Jurnal JEETech, 2023)
An overhaul is a process of dismantling a problematic engine so that it can be examined more thoroughly. During the overhaul, the problematic engine components are replaced. The overhaul of the sphere gap setting of the semi-automatic high impulse voltage generation is also intended to maximize the K3 system and the level of accuracy when conducting research on impulse voltage generation. The current condition after the occurrence of damage to the automatic sphere gap adjustment machine. The sphere gap setting is done manually, causing the desired ball gap distance to be not very accurate, and the risk of work accidents is higher in the high voltage laboratory. In the first stage of work, an inspection and measurement were carried out to replace the capacitor and limit switch components because they could no longer be used. As well as improvements to the electromagnetic brake components. From the test results, it was found that the distance measurement was as expected and it can be proven that after an overhaul, the semi-automatic spacer can function normally again so it can make it easier to conduct high voltage impulse research. In addition, from a security point of view, it is better because the spacing between the balls is done outside the high-voltage impulse generation cage